2018
DOI: 10.1590/0100-29452018037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shading on leaf physiology and morphology in the ‘Yinhong’ grape plants

Abstract: Shading is a practical measure to reduce the heat stress to grape trees in the summer. However, inappropriate shading will cause the reduction in leaf photosynthesis and consequently the retardation of growth for the plants or the loss of fruit yield and quality for the mature grape trees. In this study we have used 1-year-old ‘YinHong’ grape plants growing under different levels of shading, ranging from full sunlight 0% to 80% reduction, to investigate their growth, physiological and biochemical responses. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…Photosynthetic activity often plays a key role in plant resistance to adverse external environmental factors; the important role of the photosynthetic pigments concentration for crop formation and the accumulation of plant bioenergy in agroecosystems is known. Photosynthesis of grape plants, being the basis of the production process, depends on many natural and anthropogenic environmental factors being geographically and climatically related [21,22,23]. Of particular importance is the photosynthesis relevance for plants that are constantly exposed to stress [24].…”
Section: Resultsmentioning
confidence: 99%
“…Photosynthetic activity often plays a key role in plant resistance to adverse external environmental factors; the important role of the photosynthetic pigments concentration for crop formation and the accumulation of plant bioenergy in agroecosystems is known. Photosynthesis of grape plants, being the basis of the production process, depends on many natural and anthropogenic environmental factors being geographically and climatically related [21,22,23]. Of particular importance is the photosynthesis relevance for plants that are constantly exposed to stress [24].…”
Section: Resultsmentioning
confidence: 99%
“…The Fv/Fm represents the energy conversion efficiency of light in the PSII reaction center, while the Fv/F0 ratio represents the activity of PSII. In this perspective, leaves of plants developed in full sun have a greater number of components of the photosynthetic apparatus, providing photosynthetic capacity per unit of leaf area [27].…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al 22 found that shading can prevent heat-stress damage of grape plants in summer. However, in our study, we examined perennial fruit vines and used a phased shading treatment to achieve ideal cooling and light transmission.…”
Section: Discussionmentioning
confidence: 99%